2016
DOI: 10.1007/s00018-016-2173-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of drug resistance in Trypanosoma brucei rhodesiense

Abstract: Trypanosoma brucei rhodesiense is one of the causative agents of human sleeping sickness, a fatal disease that is transmitted by tsetse flies and restricted to Sub-Saharan Africa. Here we investigate two independent lines of T. b. rhodesiense that have been selected with the drugs melarsoprol and pentamidine over the course of 2 years, until they exhibited stable cross-resistance to an unprecedented degree. We apply comparative genomics and transcriptomics to identify the underlying mutations. Only few mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Furthermore, T. copemani G1 has always been found in blood of marsupials while T. copemani G2 has also been found in tissues (Botero et al., 2013). Interestingly, we found that both strains of T. copemani exhibited significant differences in susceptibility to the different drugs used, supporting previous findings that genetic variation/gene varinats within species determines the degree of susceptibility to drugs (Campos et al., 2011, Plourde et al., 2012, Graf et al., 2013, Graf et al., 2016, Laffitte et al., 2016). Previous studies have shown an association between T. cruzi genetic diversity and their susceptibility to different drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T. copemani G1 has always been found in blood of marsupials while T. copemani G2 has also been found in tissues (Botero et al., 2013). Interestingly, we found that both strains of T. copemani exhibited significant differences in susceptibility to the different drugs used, supporting previous findings that genetic variation/gene varinats within species determines the degree of susceptibility to drugs (Campos et al., 2011, Plourde et al., 2012, Graf et al., 2013, Graf et al., 2016, Laffitte et al., 2016). Previous studies have shown an association between T. cruzi genetic diversity and their susceptibility to different drugs.…”
Section: Discussionmentioning
confidence: 99%
“…An unusual aminopurine transporter, TbAT1/P2, a member of the highly conserved Equilibrative Nucleoside Transporter family, facilitates uptake of both [37]. Deletion or mutation of the TbAT1/P2 gene reduces the sensitivity of T. brucei to diamidines, particularly diminazene, and melaminophenyl arsenicals [38, 39, 40, 41, 42]. …”
Section: Old and Still In The Clinic: Pentamidine And Melarsoprolmentioning
confidence: 99%
“…Further analyses revealed that aquaglyceroporin 2 ( AQP2 ) determines MPXR [44•, 45•]. Further, re-introduction of a wild-type TbAQP2 allele in even the most resistant strains fully restores drug sensitivity [45•, 46••, 47•, 41]. Indeed, expressing TbAQP2 in Leishmania mexicana promastigotes profoundly increases their sensitivity to both pentamidine and melarsoprol [45 • ].…”
Section: Old and Still In The Clinic: Pentamidine And Melarsoprolmentioning
confidence: 99%
“…Melarsoprol remains the only drug available for the treatment of second stage T. b. rhodesiense infection, yet it is highly toxic and difficult to administer (30). In addition, there have been increased reports of melarsoprol resistance and treatment failures in sub-Saharan Africa since the 1990s, only some of which have been explained by transporter mutations (3437). Since melarsoprol has been widely studied, with both known and unknown genes associated with its cytotoxicity and treatment failures, it was selected for a T. brucei GoF library proof of principle genetic screen.…”
Section: Resultsmentioning
confidence: 99%